Role of tree stand evapotranspiration in maintaining satisfactory drainage conditions in drained peatlands - Sarkkola, Sakari; Hökkä, Hannu; Koivusalo, Harri; Nieminen, Mika; Ahti, Erkki; Päivänen, Juhani; Laine, Jukka (Canadian Journal of Forest Research, 2010)
Ditch networks in drained peatland forests are maintained regularly to prevent water table rise and subsequent decrease in tree growth. The growing tree stand itself affects the level of water table through evapotranspiration, the magnitude of which is closely related to the living stand volume. In this study, regression analysis was applied to quantify the relationship between the late summer water table depth (D WT ) and tree stand volume, mean monthly summertime precipitation (P s ), drainage network condition, and latitude. The analysis was based on several large data sets from southern to northern Finland, including concurrent measurements of stand volume and summer water table depth. The identified model demonstrated a nonlinear effect of stand volume on D WT , a linear effect of P s on D WT , and an interactive effect of both stand volume and P s . Latitude and ditch depth showed only marginal influence on D WT . A separate analysis indicated that an increase of 10 m 3 ·ha –1 in stand volume corresponded with a drop of 1 cm in water table level during the growing season. In a subsample of the data, high bulk density peat showed deeper D WT than peat with low bulk density at the same stand volume.